Music therapy in pediatric and neonatal intensive care units: A systematic review and meta-analysis - Lorenz Cavalcante, Luiza; César Barbosa, Ricardo; Pires Sciarra, Adília Maria; Fernandes de Godoy, Moacir (Acta Biomedica Atenei Parmensis, 2026)
Background and aim: Music Therapy is a form of therapy that involves the musical sphere to promote the well-being and improvement of patients' vital conditions. Conversely, intensive care units are normally recognized as stressful and threatening environments. Therefore, it can be used to contribute to maintaining the mental health of these patients.Methods: A systematic review with meta-analysis of Music Therapy in pediatric and neonatal intensive care units was performed. The methodology followed the PRISMA 2020 guidelines, with 12 articles analyzed, and a total of approximately 753 patients. The vital signs assessed were perceived pain intensity, oxygen saturation, blood pressure, respiratory and heart rate. Additionally, a comparison was made between different types of music for each population studied.  Results: It was observed a reduction of respiratory rate and pain sensitivity index in the pediatric ICU by 1.92 bpm (p: 0.004) and 2.09 Wong-Baker FACES units (p: